Description of Neptosternus haibini sp. nov. from China (Coleoptera: Dytiscidae: Laccophilinae) - Peng, Yunfei; Ji, Lanzhu; Bian, Dongju; Hájek, Jiří (Zootaxa, 2018)
Neptosternus haibini sp. nov. is described from Guangdong Province, China. The new species is very similar to N. wewalkai Balke, Hendrich & Yang, 1997, from which it can be recognised only by the shape of the male genitalia. The habitus and genitalia of both species are illustrated. Neptosternus pocsi Satô, 1972 is recorded from China (Yunnan province), and the Palaearctic region, for the first time. Currently, eight species of Neptosternus are known from China; a key to Chinese Neptosternus is provided.